67 Self-rated worry predicts hospitalisation in out-of-hours services telephone triage. (16th April 2018) - Gamst-Jensen, H; Frishknecht, E; Lippert, F; Folke, F; Egerod, I; Huibers, L; Brabrand, M; Tolstrup, J; Thygesen, L
Abstract : Aim: Telephone-triage poses a challenge in estimating urgency and determining the best response in acute health care. Lack of visual cues, vague symptom description, interpretation of symptoms, and spoken word contribute to the complexity. 1 The aim of the study was to include information that would enrich the telephone-triage with a measure of the callers' subjective feeling of urgency defined as 'degree-of worry' (DOW). We tested the hypothesis that high DOW would be associated with hospitalisation within 48 hours. Method: A prospective cohort study was performed between 24.01–9.02 2017. Callers rated their DOW on a 1–5 scale (1=minimum worry, 5=maximum worry) before transferred to a call-handler. Length of hospital stay was obtained from National Patient Register. The association between DOW and hospitalisation was assessed using logistic regression. Results: Of 11 413 calls to the helpline, 581 individuals (5.1%) were hospitalised. Most of the hospitalised individuals (n=374, 64.4%) presented a high DOW (DOW 4–5). A high DOW had an odds ratio for being hospitalised of 5.38 (95% CI: 4.05 to 7.15) compared to those with a low DOW (DOW 1–2). Medium DOW (DOW 3) had intermediate odds ratio of 2.24 (95% CI 1.65 to 3.06). We observed this in all age groups, both genders, all levels of comorbidity, regardless if the caller was the patient or a close relative/friend. Conclusion: A high DOW increased the odds for hospitalisation five-fold. DOW could be beneficial in supporting assessment and clinical decision-making in telephone-triage as well as directly involving the caller in the decision-making process. Reference: . Leprohon J, Patel VL. Decision-making strategies for telephone triage in emergency medical services. Medical Decision Making: An International Journal of the Society for Medical Decision Making 1995;15:240–253. Conflict of interest: None Funding: Trygfonden, Danish Nurses Association and Laerdal Foundation.